Basic concepts of chemistry - Malone, Leo J. (Leo Jackson) 1938- (John Wiley & Sons, Inc, 1997)
The text's three main goals are to introduce chemistry as a living, relevant science, to encourage learning and critical thinking, and to help readers overcome the math difficulties that impede their progress in chemistry. Designed to help readers master the principles of general chemistry. As a prep book, it promotes active involvement with the material. There are special features throughout that reinforce concepts and help to develop strong problem solving and study skills. Updated to Include an Interactive Learning Ware problems CD containing several of the chapter ending problems from the book in an interactive tutorial with feedback to help readers set up and solve problems.